“TELETHERAPY IMPLEMENTATION AND ITS IMPACT ON SAUDI ARABIA’S HEALTHCARE SYSTEM: OPPORTUNITIES AND CHALLENGES” - Nora yazid aldeghaither; Ahmad jamal Abdo; Dr.Hamdan Aqel Almishrafi; Saleem Hidelq H Alshehabi; Abdullah ahmed alzahrani; Majed hajed qael Alotaibi; Bader Hamoud Almutairi; Hadi fahad Mohsen Al dosari (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Teletherapy implementation holds significant promise for enhancing healthcare accessibility and delivery in Saudi Arabia, aligning with the ambitious goals outlined in Saudi Vision 2030. This research paper synthesizes insights from several key academic papers to explore the opportunities and challenges associated with the integration of teletherapy into the Saudi healthcare system. Alghamdi et al. (2022) present a cross-sectional study elucidating healthcare providers' perceptions and barriers regarding the adoption of telehealth applications in the country. The findings underscore the importance of addressing various challenges, including technological infrastructure, regulatory frameworks, and cultural considerations, to facilitate widespread teletherapy implementation.Furthermore, Alhefzi (2020) outlines the imperative of incorporating telehealth elements into Saudi Vision 2030 to achieve its healthcare objectives effectively. By leveraging teletherapy, the Kingdom aims to enhance patient outcomes, improve healthcare accessibility, and optimize resource utilization. Additionally, Banjar and Alfaleh (2021) provide insights into Saudi Arabia's experience in implementing telemental health services during the COVID-19 pandemic, shedding light on the rapid adoption and adaptation of teletherapy solutions in response to emerging healthcare needs. This paper synthesizes these perspectives to offer a comprehensive analysis of the opportunities and challenges associated with teletherapy implementation in Saudi Arabia, highlighting the importance of tailored strategies to maximize its impact on the country's healthcare landscape.